KEHIDUPAN AYAM DALAM KARYA SENI LUKIS KONTEMPORER - Eki Sajri, Drs. Idran Wakidi, Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2016)
Purpose raised chicken’s life is to visual and inform the public about the life of chickens that leads to a lot of people’s lives. Creating a work, there are several stages, namely : Preparation ( tools and materials ), the stage of elaboration, synthesis, the realization of the concept, and settlement. This thesis describes the behavior more chickens that tends to lead to a lot of people's lives from how chickens lay eggs, caring for the children to raise with patience and compassion. Visual form of the work is packed with the title : Telur, Menggeram, Menetas, Perhatian, Mencari Makan, Anak Ayam, Makan, Berkokok, Berkelahi, and Sihidung Belang.Kata kunci:hasil belajar, pembelajaran Seni rupa,model pembelajaran Problem Solving.